Doença pulmonar obstrutiva crônica - VaIe, Simone Alves Do [UNESP]; Coelho, Liana Sousa [UNESP]; Tanni, Suzana Erico [UNESP]; Godoy, Irma de [UNESP] (My University, 2010)
The present review summarizes the clinical aspects, diagnostics criteria and treatment of Chronic Obstructive Pulmonary Disease (COPD). Besides, will be reviewed the systemic manifestations associated with COPD and its clinical relevance in the patient's follow up. © Copyright Moreira Jr. Editora.
Chronic obstrutive pulmonary disease
Keywords: Chronic obstructive pulmonary disease; Dyspnea; chronic obstructive lung disease; clinical feature; follow up; human; review